Anti-aging cyclophosphazene metal frame structure nano flame retardant as well as preparation and application thereof
By combining phosphazene flame retardant with metal organic frame structure, a multi-ring structure nanofire retardant is prepared, which solves the large amount of existing small molecule flame retardant used, poor effect and poor compatibility in epoxy resins. The problem of this problem achieves efficient flame retardant and anti-aging properties, improves the fluidity and transparency of epoxy resin, and reduces fire risk and heat release rate.
Patent Information
- Application Number
- CN202411489545.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing small molecule flame retardant in epoxy resin has problems such as large amounts of use, poor flame retardant effect, poor compatibility, easy precipitation failure and large amounts of smoke that are harmful to the environment. It also has poor fluidity and low transparency during processing, and is easy to Low carbon yield and single function.
Combining phosphazene flame retardant with metal organic frame structure, an anti-aging phosphazene metal frame structure nanofire retardant containing acid, gas and carbon sources is prepared, through 2-aminopyrazine and cobalt-based metal The reaction of the organic framework ZIF-67 and hexachlorocyclic triphosphazene form a nanofire retardant with a polycyclic structure.
This flame retardant has excellent flame retardant effect and anti-aging ability, improves the fluidity and transparency of epoxy resin, enhances the ultraviolet absorption capacity, and is a high-efficiency expansion flame retardant that integrates three sources and is compatible with polymer systems. , can quickly achieve flame retardant effect before the substrate is burned, reducing fire risk and heat release rate.
Smart Images

Figure CN119285978A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an anti-aging cyclophosphazene metal frame structure nano flame retardant, preparation and application thereof, and belongs to the technical field of nano materials and flame retardancy. Background Art
[0002] Epoxy resins are widely used in the fields of electronic packaging and machinery, thanks to their excellent mechanical properties and electrical insulation, as well as their ability to remain stable under various environmental conditions. In addition, epoxy resins also have a place in the field of building materials due to their low cost and easy processing and molding, such as flooring materials, pipes and waterproof coatings. Epoxy resins are widely used, of which 38% are used in the construction and coatings industry, including the reinforcement of building structures, anti-corrosion coatings and decorative coatings; 22% are used in the electronics and machinery industry, mainly for the packaging of circuit boards and capacitors and as structural materials. With the continuous growth of market demand in the manufacturing industry, the demand for epoxy resins is also increasing. Although epoxy resins have excellent mechanical properties, electrical insulation and processing properties, their flammability limits their application in certain fields, especially in situations where flame retardancy is strictly required. Since the flame of epoxy resins will not extinguish itself after leaving the fire, this undoubtedly increases the risk of fire, so it is crucial to improve their flame retardant properties.
[0003] At the same time, some epoxy resins used outdoors are exposed to sunlight for a long time. The short-wave part of ultraviolet rays (especially UV-C and part of UV-B) has high energy, which can break the chemical bonds in the epoxy chain, leading to the breakage of its molecular chain, thus causing degradation. This degradation process reduces the molecular weight of the material and affects its physical and mechanical properties. At the same time, ultraviolet radiation can accelerate the oxidation reaction of epoxy resin and generate free radicals. These free radicals further react with oxygen to form peroxides and carbonyl compounds, causing the surface of the material to become powdery, cracked, and lose gloss, while also causing the overall discoloration of the material, which is the so-called aging. In view of current needs, improving the flame retardant and anti-aging properties of polymer materials has become the focus of materials science. The flame retardancy of the material is effectively enhanced by adding phosphorus, halogen and inorganic flame retardants, while the use of UV shielding agents delays the aging of epoxy resins. However, the addition of additives introduces new challenges: combustion smoke pollution, reduced compatibility with the matrix, and potential effects on mechanical and processing properties, all of which need to be balanced in the optimization of material properties.
[0004] With the development of research on metal organic framework (MOFs) materials, the application requirements of multifunctional MOFs materials are also increasing. In particular, their combination with polymers has become a hot research field. In view of a key problem faced by polymer materials - fire risk, traditional inorganic flame retardants are often poorly compatible with polymer matrices, while organic flame retardants have problems with uneven molecular weight distribution and poor thermal stability. MOFs materials can circumvent these defects and show great potential as organic-inorganic hybrid materials. Under the action of the electric field of the surrounding ligands, the five degenerate d orbitals of the metal ions with the same energy are split. Some energies increase, while others decrease. This effect of splitting the energy level of the central ion d orbital due to the electric field of the ligand is called the coordination field effect. Some MOF materials have a large number of transition metal ions, which have partially filled d orbitals. When excited by photon energy, the electrons on the d orbitals can transition from low-energy d orbitals to high-energy d orbitals under the action of the coordination field. This electronic transition process is accompanied by the absorption of light of a specific wavelength, thus producing a unique absorption spectrum. This transition is called dd electronic transition, also known as coordination field transition. This phenomenon not only enriches the types of organic UV shielding materials, but also provides new possibilities for the development of high-performance UV protection materials.
[0005] Phosphazene flame retardants are known for their unique PN atom alternating main chain structure, showing the variability of cyclic or linear structures and excellent flame retardant effects. This type of flame retardant not only has outstanding thermal stability and excellent antioxidant properties, but also has good biocompatibility and biodegradability. At the same time, their optical and mechanical physical properties are also very outstanding. Combining the advantages of inorganic and organic compounds, phosphazene flame retardants effectively improve material properties through the synergistic effect of PN. In particular, hexachlorocyclotriphosphazene, as a typical phosphazene flame retardant, has a six-membered ring structure constructed with a PN skeleton, which gives it extremely high thermal stability and flame retardancy. The π-π conjugation effect in this structure enhances its ability to absorb ultraviolet rays, and the high activity of the phosphorus-chlorine bond enables it to react efficiently with active functional groups such as hydroxyl groups, making it easy to synthesize customized flame retardants.
[0006] There is currently no report on the combination of MOFs materials with phosphazene flame retardants. Summary of the invention
[0007] In order to overcome the problems of large dosage, poor flame retardant effect, poor compatibility with base materials, easy precipitation failure and generation of large amounts of smoke that are harmful to the environment, the epoxy resin has poor fluidity and low transparency during processing, and at the same time, the problem of low carbonization rate and single function of some small molecule flame retardants, the purpose of the present invention is to provide an anti-aging cyclophosphazene metal framework structure nano flame retardant, preparation and application. The phosphazene flame retardant and metal organic framework are combined to obtain an anti-aging phosphazene metal framework structure flame retardant containing acid source, gas source and carbon source.
[0008] To achieve the above objectives, the technical solution of the present invention is as follows.
[0009] A method for preparing an anti-aging cyclophosphazene metal framework structure nano flame retardant, the method steps comprising:
[0010] 2-Aminopyrazine and cobalt-based metal organic framework ZIF-67 are dissolved in an organic solvent, heated to 55-80°C, and a hexachlorocyclotriphosphazene solution is added. The mixture is heated, stirred and refluxed for 8-24 hours. After the reaction is completed, the precipitate is collected, washed and vacuum dried to obtain an anti-aging cyclophosphazene metal framework structure nano flame retardant.
[0011] Preferably, the mass ratio of 2-aminopyrazine, ZIF-67 and hexachlorocyclotriphosphazene is 1:1 to 10:1 to 4. More preferably, the mass ratio of 2-aminopyrazine, ZIF-67 and hexachlorocyclotriphosphazene is 1:2 to 6:2 to 3.
[0012] Preferably, the organic solvent is one or more of tetrahydrofuran, anhydrous acetonitrile, acetone and dichloromethane.
[0013] Preferably, the solvent of the hexachlorocyclotriphosphazene solution is tetrahydrofuran.
[0014] Preferably, the hexachlorocyclotriphosphazene solution is added within 30 minutes.
[0015] Preferably, the reaction temperature is 60-70° C. and the reaction time is 12-18 h.
[0016] Preferably, the stirring rate is 300-400 rpm.
[0017] Preferably, the drying temperature is 50-70° C. and the drying time is 8-16 hours.
[0018] Preferably, the cobalt-based metal organic framework ZIF-67 is prepared by the following method, and the method steps include: dissolving cobalt nitrate hexahydrate in solvent A to obtain a cobalt salt solution; dissolving 2-methylimidazole in solvent B to obtain a 2-methylimidazole solution; adding the 2-methylimidazole solution to the cobalt salt solution, standing at 15 to 40° C. for 8 to 32 hours, and after standing, centrifuging at a speed of 6000 to 12000 rad / min for 3 to 8 minutes, washing with anhydrous ethanol, and drying at 50 to 70° C. for 8 to 16 hours to obtain ZIF-67.
[0019] Preferably, the molar ratio of cobalt nitrate hexahydrate to 2-methylimidazole is 1:4 to 10. More preferably, the molar ratio of cobalt nitrate hexahydrate to 2-methylimidazole is 1:4 to 6.
[0020] Preferably, the standing temperature is 25-35°C.
[0021] Preferably, the centrifugation time is 4 to 6 minutes.
[0022] Preferably, the solvent A and solvent B are respectively one or more of anhydrous methanol, anhydrous ethanol and water.
[0023] An anti-aging cyclophosphazene metal framework structure nano flame retardant is prepared by the above method.
[0024] An application of the anti-aging cyclophosphazene metal framework structure nano flame retardant of the present invention, wherein the flame retardant is used as a flame retardant of a polymer system.
[0025] Beneficial Effects
[0026] The present invention provides an anti-aging cyclophosphazene metal framework structure nano flame retardant, which has excellent flame retardant effect and anti-aging ability. The multi-ring structure of the flame retardant makes it have higher flame retardant efficiency and better dispersibility, and can increase the fluidity and transparency in the epoxy resin processing process, so as to better cooperate, and the presence of the multi-ring structure can enhance the absorption of ultraviolet rays. At the same time, the introduction of the metal organic framework can promote the formation of smoke and heat insulation carbon layer, improve the flame retardant effect, and the introduction of transition metals can further enhance the anti-aging ability of the flame retardant (especially the anti-ultraviolet absorption ability). Compared with the existing single-chain or branched phosphorus / nitrogen flame retardants, the small molecule cyclophosphazene metal framework structure nano flame retardant has a more excellent synergistic flame retardant effect.
[0027] This flame retardant is a highly efficient intumescent flame retardant that integrates three sources (acid source, gas source, and carbon source). It does not need to be used in combination with other flame retardants. After being added, it has no obvious loss of mechanical properties of polymer materials such as epoxy resin. It has good compatibility with the polymer system matrix, and its decomposition temperature matches that of the matrix. It can quickly play a flame retardant role before the matrix burns. At the same time, it can increase the fluidity of the matrix, which is conducive to processing and molding, increase the transparency of the matrix, and facilitate color adjustment.
[0028] When the flame retardant is added to the flame retardant epoxy resin at a dosage of 2%, the vertical combustion test grade can reach UL-94V0 level; the peak heat release rate can be reduced by 35%, and the total heat release can be reduced by 28%. It can also increase the UV shielding ability of the epoxy resin system by 40%. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a scanning electron microscope image of the intermediate purple powder ZIF-67 synthesized in Example 1 of the present invention.
[0030] Figure 2 This is a scanning electron microscope image of the cyclophosphazene metal framework structure nano flame retardant synthesized in Example 1 of the present invention.
[0031] Figure 3 This is a transmission electron micrograph of the cyclophosphazene metal framework structure nano flame retardant synthesized in Example 1 of the present invention.
[0032] Figure 4 This is an EDS image of the cyclophosphazene metal framework structure nano flame retardant synthesized in Example 1 of the present invention.
[0033] Figure 5 This is a graph of the peak heat release rate of the epoxy resin and its composite system in Example 1 of the present invention.
[0034] Figure 6 This is the total smoke release diagram of the epoxy resin and its composite system in Example 1 of the present invention.
[0035] Figure 7 This is an infrared comparison chart of the release of ether compounds after the epoxy resin and its composite system are burned in Example 1 of the present invention.
[0036] Figure 8 This is an infrared comparison chart of aromatic compound release after combustion of the epoxy resin and its composite system in Example 1 of the present invention.
[0037] Fig. 9 This is an infrared comparison chart of hydrocarbon release after combustion of the epoxy resin and its composite system in Example 1 of the present invention.
[0038] Fig.10 Graph showing the ultraviolet transmittance of the epoxy resin and its composite system in Example 1 of the present invention. DETAILED DESCRIPTION
[0039] The present invention will be further described in detail below in conjunction with specific embodiments.
[0040] 3.64 g of cobalt nitrate hexahydrate was added to 50 mL of anhydrous ethanol and ultrasonicated for 5 min until the system was uniformly mixed as solution A. Solution A was then poured into a 200 mL beaker. 4.12 g of 2-methylimidazole was dissolved in 50 mL of anhydrous ethanol and ultrasonicated for 5 min as solution B. Solution B was added to the beaker containing solution A, sealed and allowed to stand at 30°C for 24 h, then transferred to a centrifuge and centrifuged at 8000 rad / min for 5 min, then washed twice with 10 mL of anhydrous ethanol, dried in a vacuum oven at 50°C and 1 KPa for 12 h to constant weight, and the reaction intermediate purple powder ZIF-67 was obtained. Its scanning electron microscopy is as follows Figure 1 shown.
[0041] Weigh 2g of 2-aminopyrazine and 3g of ZIF-67, dissolve them in 150mL tetrahydrofuran solution, ultrasonicate for 10min until uniformly dispersed, as solution C, then add solution C to a 250mL three-necked flask, connect a 100mL constant pressure dropping funnel, magnetic stirring, 24-mouth serpentine condenser, and tail gas receiving and processing device, and stir and heat at 70°C. Dissolve 1g of hexachlorocyclotriphosphazene in 35mL tetrahydrofuran solution, stir until clear and transparent at room temperature and pressure, as solution D, then add solution D to a constant pressure funnel, adjust the flow rate for 30min to drip, continue stirring and reacting for 8h, filter the precipitate, and then wash it three times with 10mL tetrahydrofuran and 10mL acetone alternately, and then dry it in a vacuum oven at 60°C and 1KPa for 8h to obtain 4.386g of green powder flame retardant with a yield of 73.1%. The scanning electron microscopy, transmission electron microscopy and EDS results of the flame retardant are as follows Figure 2-4 shown.
[0042] 150g of epoxy resin E-44 was used as the matrix, poured into a 200mL beaker, and mechanically stirred at 80°C under open conditions at a speed of 400r / min. At the same time, 35g of 4,4'-diaminodiphenylmethane was weighed as a curing agent in a 50mL beaker and placed in a 120°C oven for 20min to melt it. Subsequently, 3.75g of the flame retardant prepared in this embodiment was dissolved in 30mL of acetone, ultrasonically treated for 5 minutes, and poured into the epoxy resin system for further stirring after being evenly dispersed. After about 30min, the acetone in the epoxy system was completely volatilized, and the molten curing agent was poured into the epoxy resin system and stirred for 1min until the system was uniform, and then the system was poured into a mold and cured at 130°C for 4h to obtain an epoxy resin composite material.
[0043] The obtained epoxy resin composite material was subjected to a limiting oxygen index test (LOI), and the measured limiting oxygen index value was 27.9%. The flame retardant grade obtained by the vertical combustion experiment test (UL-94) was V-1. Further cone calorimeter test was carried out, and the peak heat release rate was reduced by 40.2% relative to the pure epoxy system, the total heat release was reduced by 29.1% relative to the pure epoxy system, the carbon dioxide production rate was reduced by 45%, and the carbon monoxide production rate was reduced by 1%. The epoxy system was also subjected to mechanical property tests and ultraviolet diffuse reflection tests. The results showed that the tensile strength of the epoxy composite system was not significantly different from that of the pure epoxy system, the ultraviolet transmittance was reduced by 45%, and the peak heat release rate and total smoke release of the epoxy resin and its composite system were as follows: Figure 5 , 6 The infrared comparison of ether, aromatic and hydrocarbon release after the combustion of epoxy resin and its composite system is shown in Figure 7-9 As shown in the figure, the UV transmittance is Fig.10 shown.
[0044] Example 2
[0045] 7.28 g of cobalt nitrate hexahydrate was added to 100 mL of anhydrous ethanol and ultrasonically mixed for 5 min until the system was uniformly mixed as solution A. Solution A was then poured into a 250 mL beaker. 8.24 g of 2-methylimidazole was dissolved in 100 mL of anhydrous ethanol and ultrasonically mixed for 5 min as solution B. Solution B was added to the beaker containing solution A. The beaker was sealed and allowed to stand at 30°C for 24 h, then transferred to a centrifuge and centrifuged at 8000 rad / min for 5 min. The beaker was then washed twice with anhydrous ethanol and dried in a vacuum oven at 50°C and 1 KPa for 12 h to constant weight to obtain the reaction intermediate ZIF-67.
[0046] Weigh 4g of 2-aminopyrazine and 6g of ZIF-67, dissolve in 250mL tetrahydrofuran solution, ultrasonicate for 10min until uniformly dispersed, as solution C, then add solution C to a 500mL three-necked flask, connect a 100mL constant pressure dropping funnel, magnetic stirring, 24-mouth serpentine condenser, and tail gas receiving and processing device, and stir and heat at 70°C. Dissolve 2g of hexachlorocyclotriphosphazene in 70mL tetrahydrofuran solution, stir until clear and transparent at room temperature and pressure, as solution D, then add solution D to a constant pressure funnel, adjust the flow rate for 30min to drip, continue stirring the reaction for 12h, filter the precipitate, and then wash it three times with 20mL tetrahydrofuran and 20mL acetone alternately, then dry it in a vacuum oven at 60°C and 1KPa for 12h to obtain 8.726g of green powder flame retardant with a yield of 72.7%.
[0047] 150g of epoxy resin E-44 was used as the matrix, poured into a 200mL beaker, and mechanically stirred at 80°C under open conditions at a speed of 400r / min. At the same time, 35g of 4,4'-diaminodiphenylmethane was weighed as a curing agent in a 50mL beaker and placed in a 120°C oven for 20min to melt it. Subsequently, 3.75g of the flame retardant prepared in this embodiment was dissolved in 30mL of acetone, ultrasonically treated for 5 minutes, and poured into the epoxy resin system for further stirring after being evenly dispersed. After 30min, the acetone in the epoxy system was completely volatilized, and the molten curing agent was poured into the epoxy resin system and stirred for 1min until the system was uniform, then the system was poured into a mold and cured at 130°C for 4h to obtain an epoxy resin composite material.
[0048] The obtained epoxy resin composite material was subjected to a limiting oxygen index test (LOI), and the measured limiting oxygen index value was 28.2%. The flame retardant grade obtained by the vertical combustion test (UL-94) was V-grade. Further cone calorimeter test was carried out, and the peak heat release rate was reduced by 39.4% relative to the pure epoxy system, the total heat release was reduced by 28.3% relative to the pure epoxy system, the carbon dioxide yield was reduced by 43%, and the carbon monoxide yield was reduced by 38%. The epoxy system was also subjected to mechanical property tests and ultraviolet diffuse reflection tests. The results showed that the tensile strength of the epoxy composite system was not significantly different from that of the pure epoxy system, and the ultraviolet transmittance was reduced by 38%.
[0049] Example 3
[0050] 14.5 g of cobalt nitrate hexahydrate was added to 300 mL of anhydrous ethanol and ultrasonically mixed for 10 min until the system was uniformly mixed as solution A. Solution A was then poured into a 1000 mL beaker. 16.48 g of 2-methylimidazole was dissolved in 300 mL of anhydrous ethanol and ultrasonically mixed for 10 min as solution B. Solution B was added to the beaker containing solution A. The beaker was sealed and allowed to stand at 30°C for 24 h, then transferred to a centrifuge and centrifuged at 8000 rad / min for 5 min. The mixture was then washed twice with anhydrous ethanol and dried in a vacuum oven at 50°C and 1 KPa for 12 h to constant weight to obtain the reaction intermediate ZIF-67.
[0051] Weigh 6g of 2-aminopyrazine and 9g of ZIF-67, dissolve in 300mL tetrahydrofuran solution, ultrasonicate for 10min until uniformly dispersed, as solution C, then add solution C to a 500mL three-necked flask, connect a 100mL constant pressure dropping funnel, magnetic stirring, 24-mouth serpentine condenser, and tail gas receiving and processing device, and stir and heat at 70°C. 3g of hexachlorocyclotriphosphazene was dissolved in 70mL tetrahydrofuran solution, stirred until clear and transparent at room temperature and pressure, as solution D, then added solution D to a constant pressure funnel, adjusted the flow rate for 30min to drip, continued to stir and react for 16h, filtered the precipitate, and then washed alternately three times with 20mL tetrahydrofuran and 20mL acetone, and then dried in a vacuum oven at 60°C and 1KPa for 16h to obtain 13.56g of green powder flame retardant with a yield of 75.3%.
[0052] 150g of epoxy resin E-44 was used as the matrix, poured into a 200mL beaker, and mechanically stirred at 80°C under open conditions at a speed of 400r / min. At the same time, 35g of 4,4'-diaminodiphenylmethane was weighed as a curing agent in a 50mL beaker and placed in a 120°C oven for 20min to melt it. Subsequently, 3.75g of the flame retardant prepared in this embodiment was dissolved in 30mL of acetone, ultrasonically treated for 5 minutes, and poured into the epoxy resin system for further stirring after being evenly dispersed. After 30min, the acetone in the epoxy system was completely volatilized, and the molten curing agent was poured into the epoxy resin system and stirred for 1min until the system was uniform, then the system was poured into a mold and cured at 130°C for 4h to obtain an epoxy resin composite material.
[0053] The obtained epoxy resin composite material was subjected to a limiting oxygen index test (LOI), and the measured limiting oxygen index value was 27.8%. The flame retardant grade obtained by the vertical combustion test (UL-94) was V-0. Further cone calorimeter test was carried out, and the peak heat release rate was reduced by 37.7% relative to the pure epoxy system, the total heat release was reduced by 27.6% relative to the pure epoxy system, the carbon dioxide yield was reduced by 42%, and the carbon monoxide yield was reduced by 40%. The epoxy system was also tested for mechanical properties and ultraviolet diffuse reflection. The results showed that the tensile strength of the epoxy composite system was not significantly different from that of the pure epoxy system, and the ultraviolet transmittance was reduced by 41%.
[0054] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.
Claims
1. A method for preparing an anti-aging cyclophosphazene metal framework structure nano flame retardant, characterized in that: The method steps include: 2-Aminopyrazine and cobalt-based metal organic framework ZIF-67 are dissolved in an organic solvent, heated to 55-80°C, and a hexachlorocyclotriphosphazene solution is added. The mixture is heated, stirred and refluxed for 8-24 hours. After the reaction is completed, the precipitate is collected, washed and vacuum dried to obtain an anti-aging cyclophosphazene metal framework structure nano flame retardant.
2. The method for preparing an anti-aging cyclophosphazene metal framework structure nano flame retardant according to claim 1, characterized in that: The mass ratio of the 2-aminopyrazine, ZIF-67 and hexachlorocyclotriphosphazene is 1:1-10:1-4; preferably, the mass ratio of the 2-aminopyrazine, ZIF-67 and hexachlorocyclotriphosphazene is 1:2-6:2-3.
3. The method for preparing an anti-aging cyclophosphazene metal framework structure nano flame retardant according to claim 1, characterized in that: The organic solvent is one or more of tetrahydrofuran, anhydrous acetonitrile, acetone and dichloromethane; the solvent of the hexachlorocyclotriphosphazene solution is tetrahydrofuran.
4. The method for preparing an anti-aging cyclophosphazene metal framework structure nano flame retardant according to claim 1, characterized in that: The hexachlorocyclotriphosphazene solution was added completely within 30 minutes.
5. The method for preparing an anti-aging cyclophosphazene metal framework structure nano flame retardant according to claim 1, characterized in that: The reaction temperature is 60-70° C., and the reaction time is 12-18 h; preferably, the stirring rate is 300-400 rpm.
6. The method for preparing an anti-aging cyclophosphazene metal framework structure nano flame retardant according to claim 1, characterized in that: The drying temperature is 50-70°C and the drying time is 8-16 hours.
7. The method for preparing an anti-aging cyclophosphazene metal framework nano flame retardant according to claim 1, characterized in that: The cobalt-based metal organic framework ZIF-67 is prepared by the following method, which includes the following steps: dissolving cobalt nitrate hexahydrate in solvent A to obtain a cobalt salt solution; dissolving 2-methylimidazole in solvent B to obtain a 2-methylimidazole solution; adding the 2-methylimidazole solution to the cobalt salt solution, standing at 15 to 40° C. for 8 to 32 hours, and after standing, centrifuging at a speed of 6000 to 12000 rad / min for 3 to 8 minutes, washing with anhydrous ethanol, and drying at 50 to 70° C. for 8 to 16 hours to obtain ZIF-67.
8. The method for preparing an anti-aging cyclophosphazene metal framework nano flame retardant according to claim 7, characterized in that: The molar ratio of cobalt nitrate hexahydrate to 2-methylimidazole is 1:4-10; preferably, the molar ratio of cobalt nitrate hexahydrate to 2-methylimidazole is 1:4-6; The standing temperature is 25-35°C; The centrifugation time is 4 to 6 minutes; The solvent A and the solvent B are respectively one or more of anhydrous methanol, anhydrous ethanol and water.
9. An anti-aging cyclophosphazene metal framework structure nano flame retardant, characterized in that: It is prepared by the method according to any one of claims 1 to 8.
10. An application of the anti-aging cyclophosphazene metal framework structure nano flame retardant as claimed in claim 9, characterized in that: The flame retardant is used as a flame retardant for a polymer system.
Citation Information
Patent Citations
Hexaimidazolecyclotriphosphazene flame retardant with surface modified by ZIF-67 nanocrystals and preparation method thereof
CN110396202A
Phosphazene-based organometallic complex flame-retardant epoxy resin and preparation method thereof
CN111635618A
Polyphosphazene derivative flame retardant for toughening and flame-retardant polylactic acid and preparation method of polyphosphazene derivative flame retardant
CN115433361A
Reactive flame retardant containing DOPO group and nitrogen heterocyclic ring and preparation method and application thereof
CN115612176A